Unexpected identification of peak systolic velocity in the radial artery as a risk factor for functional primary patency of radiocephalic fistulas - Rui Cong; Songxiu Li; Shasha Shi (Nefrología)
Objective: As radiocephalic fistula is not necessarily appropriate for all patients with advanced kidney disease, our aim was to investigate the sensitive indicators that affect the functional primary patency of radiocephalic fistulas. Methods: This prospective observational study included consecutive patients referred to the Second Hospital of Dalian Medical University for initial creation of radiocephalic fistula from July 2017 to December 2019. Preoperative ultrasound parameters, demographic characteristics, serum indicators and comorbidities were recorded. The functionality of radiocephalic fistulas would be assessed every 6 months until March 2023, following their unassisted maturation, unless AVF dysfunction, kidney transplantation, mortality or loss to follow-up occurred. Kaplan–Meier analysis was employed to illustrate differences in functional primary patency of radiocephalic fistulas, while log-rank tests were utilized to compare survival curves. Univariate and multivariable Cox proportional hazard models were performed, yielding hazard ratios and 95% confidence intervals. The significance level was set at 5% for a two-sided test. Results: The studies included a total of 182 patients who successfully underwent radiocephalic fistulas with primary unassisted maturation. The mean age of the study population was 58 years, with 66 percent being male. All AVFs were placed on the forearm, with 84% located on the left side.The primary patency rates of eleven parameters exhibited significant differences between groups stratified by cut-off values at different time points. Notably, the group with a peak systolic velocity of the radial artery near the elbow ≤59 cm/s demonstrated a higher primary patency rate compared to the >59 cm/s group at 2 years (78.4% vs 57.5%, P = 0.026).In the univariate Cox proportional hazard models, the P values for gender, the diameter of radial artery near the elbow, the peak systolic velocity of radial artery near the elbow, the diameter of brachial artery near the elbow were less than 0.1. The multivariable Cox proportional hazard model revealed that only the peak systolic velocity of radial artery near the elbow exhibited a significant impact on the functional primary patency of radiocephalic fistula (HR = 1.017, 95%CI 1.002–1.031, P = 0.021). Conclusions: The peak systolic velocity of the radial artery near the elbow is a significant risk factor for functional primary patency of radiocephalic fistula. Preoperative evaluation of the peak systolic velocity could allow to identify patients with a lower likelihood of long-term radiocephalic fistula patency, facilitating improved selection of candidates for radiocephalic fistula creation. Resumen: Objetivo: Dado que la fístula radiocefálica no es necesariamente adecuada para todos los pacientes con enfermedad renal avanzada, nuestro objetivo consistió en investigar los indicadores sensibles que afectan la supervivencia primaria funcional de las fístulas radiocefálicas. Métodos: Este estudio prospectivo observacional incluyó pacientes consecutivos remitidos al Segundo Hospital de la Universidad de Medicina de Dalian para someterse a la creación inicial de una fístula radiocefálica entre julio de 2017 y diciembre de 2019. Se registraron los parámetros ecográficos preoperatorios, las características demográficas, los indicadores séricos y las comorbilidades. La funcionalidad de las fístulas radiocefálicas se evaluaría cada 6 meses hasta marzo de 2023, siguiendo su maduración natural, a menos que ocurriera disfunción del acceso vascular, trasplante renal, mortalidad o pérdida en el seguimiento. Se utilizó el análisis de Kaplan-Meier para ilustrar las diferencias en la permeabilidad primaria funcional de las fístulas radiocefálicas, mientras que se emplearon pruebas log-rank para comparar las curvas de supervivencia. Se realizaron modelos univariables y multivariables mediante regresión proporcional Cox para obtener razones e intervalos de confianza del riesgo (hazard ratio) con un nivel significativo establecido en un 5% para una prueba bilateral. Resultados: El estudio incluyó un total de 182 pacientes que se sometieron exitosamente a fístulas radiocefálicas con maduración primaria no asistida. La edad promedio de la población estudiada fue de 58 años, con un 66 por ciento de hombres. Todas las AVF se ubicaron en el antebrazo, siendo el 84% en el lado izquierdo.Las tasas de permeabilidad primaria para once parámetros mostraron diferencias significativas entre los grupos estratificados por valores límite en diferentes momentos. Es importante destacar que el grupo con una velocidad sistólica máxima de la arteria radial cerca del codo ≤59 cm/s demostró una tasa mayor de permeabilidad primaria en comparación con el grupo >59 cm/s a los 2 años (78,4% frente al 57,5%, p = 0,026).En los modelos univariados de riesgo proporcional de Cox, se observaron valores de P inferiores a 0,1 para el sexo, el diámetro de la arteria radial cerca del codo, la velocidad sistólica máxima de la arteria radial cerca del codo y el diámetro de la arteria braquial cerca del codo. El modelo multivariable de riesgo proporcional de Cox reveló que únicamente la velocidad sistólica máxima de la arteria radial cerca del codo tuvo un impacto significativo en relación con la permeabilidad primaria funcional de las fístulas radiocefálicas (HR= 1,017; ic95% 1,002-1,031; P= 0,021). Conclusiones: La velocidad sistólica máxima de la arteria radial en proximidad al codo constituye un factor de riesgo significativo para la permeabilidad primaria funcional de la fístula radiocefálica. La evaluación preoperatoria de dicha velocidad puede contribuir a identificar pacientes con una menor probabilidad de mantener una fístula radiocefálica permeable a largo plazo, lo cual facilitaría una mejor selección de candidatos para su.